(untitled) (Journal of Forensic Medicine & Toxicology, 2015)
Background & objectives: In Gujarat sale, possession, purchase, consumption has been banned by law in force (Bombay Prohibition Act, 1949). Even though smuggling and illicit sale of alcohol are very common &illegal consumption of alcohol is prevalent in almost all classes of society. Present study has been conducted to study the epidemiological and other aspects like BAC. Methods: Present study was conducted retrospectively for period of 3 years from 2012-14 in the cases brought at District Hospital, Himmatnagar for Medico legal examination with alleged history of consumption of alcoholic beverage. Results: Observations show male predominance with maximum case in age group of 21-40 years with maximum case at evening and night time. Maximum cases with BAC>0.05gm%. Interpretation & Conclusion: Cases of drunkenness are on rise even after legal prohibition and mortality resulted from hooch tragedy of july,2009.